The Limits of Epistemic Communities: EU Security Agencies - Cross, Mai'a K. Davis (2015)
This article examines the cases of the European Defence Agency (EDA) and EU Intelligence Analysis Centre (IntCen) to argue that although they are comprised of high-level security experts, they do not constitute epistemic communities. Research on other groups of security experts based in Brussels has shown that epistemic communities of diplomats, military experts, security researchers, and civilian crisis management experts, among others, have been able to influence the trajectory of security integration by virtue of their shared knowledge. Importantly, these security epistemic communities have been shown to significantly impact outcomes of EU security policy beyond what would be expected by looking only at member-states’ initial preferences. In exploring two examples of “non-cases” that are at the same time very similar to the other examples, the author seeks to shed light on why some expert groups do not form epistemic communities, and how this changes the nature of their influence. In so doing, the goal is to sharpen the parameters of what constitutes epistemic communities, and to add to our understanding of why they emerge. The argument advanced in this article is that institutional context and the nature of the profession matter as preconditions for epistemic community emergence.